Enhancing Technology Competence among Primary Students through STEAM Lessons Applying the Design Thinking Process - Nguyen, Hoai-Nam; Nguyen, Hong-Duong; Ta, Thanh-Trung (Revija za elementarno izobraževanje, 2024)
This study seeks to evaluate the impact of integrating elements of arts and humanities education into the topic of STEAM on the formation and development of students’ competence. The paper suggests a procedure for teaching STEAM subjects using design thinking approaches. Then, technology-related lessons were covered in practical pedagogical activities for grade 3 pupils at three primary schools in Hai Phong, Vietnam. The findings demonstrate that the suggested STEAM subject teaching methodology is workable and helps students develop eight distinctive behavioural markers of technical competence. As a result, this study offers primary school instructors a strategy for implementing STEAM instruction.
Keywords: STEAM education, design thinking, technical competence, technology in primary school.